2016
DOI: 10.3109/0284186x.2015.1115119
|View full text |Cite
|
Sign up to set email alerts
|

Trends in gynecologic cancer among elderly women in Denmark, 1980–2012

Abstract: Background The aim of this analysis was to describe trends in incidence, mortality, prevalence, and survival in Danish women with gynecologic cancer from 1980-2012 comparing women aged 70 years or more with younger women. Material and methods Gynecologic cancers included were ICD-10 codes C53 (cancer of the cervix uteri), C54 (corpus uteri cancer), C56 (ovarian cancer) and C57 (Fallopian tube cancer). Data derived from the NORDCAN database with comparable data on cancer incidence, mortality, prevalence and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…Major improvements in the diagnosis and the treatment of BC and GOC have led to an increase in overall survival rates . One of the most important goals of practitioners is to improve the quality of life of the patients affected by these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Major improvements in the diagnosis and the treatment of BC and GOC have led to an increase in overall survival rates . One of the most important goals of practitioners is to improve the quality of life of the patients affected by these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…23,54,55 In most other countries, mortality rates are decreasing 4,18,19,56 or stable. 17,23,54 The current study showed significantly decreasing mortality trends during the period 1994Y2013 in Ireland, NI (since 2005), and Israeli Jews, which are consistent with the observations for other high-background-mortality countries (ie, the United States, for the period 1975Y2011).…”
Section: Mortality Trendsmentioning
confidence: 99%
“…The majority of studies compare the long-term outcomes between elderly and young patients. The mortality rates of patients treated for cervical cancer who are more than 70 years old are typically 2-3-fold higher in comparison to younger women [2]. A few studies distinguished the group of women treated for cervical cancer more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Although cervical cancer is more common in young women, it is certainly present in postmenopausal and elderly women [4]. Furthermore, while the incidence of cervical cancer among younger patients has decreased, the proportion of patients diagnosed who are over 70 years of age has remained stable (near 18%) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation